Application of indoline dyes having a carboxylated 1, 3-indandione ring linked with thienyl or hexylthienyl ring to dye-sensitized solar cells. (December 2017) - Matsui, Masaki; Kimura, Ryosuke; Kubota, Yasuhiro; Funabiki, Kazumasa; Manseki, Kazuhiro; Jin, Jiye; Hansuebsai, Aran; Inoue, Yukiko; Higashijima, Shinji
Abstract: The performance of a new indoline dye having a carboxylated 1, 3-idandione unit linked with a hexythienyl ring showed higher conversion efficiency than the analogous dye without the hexyl group. Graphical abstract: Highlights: A novel indoline dye with a carboxylated 1, 3-indadione linked with a hexylthienyl ring. Suitable energy levels and fluorescence lifetime. The hexyl group is important to exhibit high efficiency.